Influence of rainfall characteristics on first flush behaviour - Zuraini, Noor Atiqah (2020)
Urban stormwater with impervious surface often produces runoff with a variety of contaminants. This paper discusses an investigation into the influence of rainfall characteristics toward the first flush behaviour. This study involved field investigations, sampling of urban stormwater runoff, laboratory testing and data analysis. 15 stormwater samples were collected and executed manually in a small catchment, which represents the higher institution area in Skudai, Johor. Data collections were carried out on 9 November 2017. Correlation of pollutants such as total suspended solids (TSS), total dissolved solids (TDS), biological oxygen demand (BOD), chemical oxygen demand (COD) and zinc with runoff were derived within the evaluation of hyetograph, hydrographs and pollutographs. The concentration varied at different stages of the same rainfall event. The higher strength of first flush was seen in case of TSS, BOD and zinc compared to TDS and COD. The finding shows that high rainfall intensity in the beginning of the event had contributed to the high wash off of some pollutants such as TSS, BOD and zinc. The concept of the first flush cannot be used alone to establish a reliable methodology to design treatment facilities. Additional knowledge and information are necessary.